Finanzierung der Zentralasienexpedition Sven Hedins: "Strengste Geheimhaltung wird von allen Beteiligten als unerlässlich angesehen" - Böhm, Hans (ERDKUNDE, 2003)
The Central Asia Expedition of the last great overland traveller in history (Beck 1971) was not financed by German Lufthansa, as has been stated in literature with reference to Sven Hedin. Lufthansa - not unlike the DFG in 1940 - acted merely as the accounting department for financial pledges made by the German Government. As arranged with Stresemann, who was the foreign minister in 1926, funding for the expedition was given subject to the condition that financial support was not to be made public. Posing as additional scientific staff, German military personnel were to partake in the enterprise under the cover of Lufthansa. Excessive expenditure for the expedition not only aroused the suspicion of espionage in Chinese military circles, but also in scientific ones. The protests of nationally-minded academics had the effect of allowing the expedition or mission to proceed only if accompanied by a substantial number of Chinese scientists. In the following years the contract regarding this point became obligatory for all foreign travellers engaged in research. In the Spring of 1928 Hedin was called back to Europe, since the government in Sinkiang refused the right to use Chinese air space, and the German government withdrew its grant.